Legume genetic resources: management, diversity assessment, and utilization in crop improvement - Upadhyaya, Hari D.; Dwivedi, S.L.; Ambrose, M.; Ellis, N.; Berger, J.; Smykal, P; Debouck, Daniel G.; Duc, G.; Dumet, D.; Flavell, A; Sharma, S.K.; Mallikarjuna, N; et al. (Springer, 2011)
Grain legumes contribute significantly to total world food production. Legumes are the primary source of dietary proteins in many developing countries, where protein hunger and malnutrition are widespread. Grain legumes germplasm constitute ~15% of the 7.4 M accessions preserved globally. Nearly, 78% of the CGIAR’s, 0.217 M accessions, have been characterized, compared to 34% of national genebank collections. Interestingly, limited data on grain quality are available as the primary focus has been on morpho-agronomic traits. Clearly, more resources should be targeted on biochemical evaluation to identify nutritionally rich and genetically diverse germplasm. The formation of core and mini core collections has provided crop breeders with a systematic yet manageable entry point into global germplasm resources. These subsets have been reported for most legumes and have proved useful in identifying new sources of variation. They may however not eliminate the need to evaluate entire collections, particularly for very rare traits. Molecular characterization and association mapping will further aid to insights into the structure of legume diversity and facilitate greater use of collections. The use of high resolution elevational climate models has greatly improved our capacity to characterize plant habitats and species’ adaptive responses to stresses. Evidence suggests that there has been increased use of wild relatives as well as new resources resulting from mutagenesis to enhance the genetic base of legume cultigens.